2022
DOI: 10.1186/s12888-022-04381-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of an Intensive Inpatient Psychotherapy Program for Chronic Depression: A naturalistic comparison with wait list

Abstract: Background Patients with chronic depression (CD) typically have an early symptom onset, more psychiatric comorbidities, more treatment attempts, and more frequent and longer inpatient hospitalizations than patients with major depressive disorders. The main purpose of this study was to investigate the effectiveness of an intensive inpatient psychotherapy program for patients with chronic depression (CD). The primary research question was whether two intensive psychodynamic inpatient treatments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
(61 reference statements)
2
1
0
Order By: Relevance
“…A recent meta-analysis on effectiveness of routinely delivered psychotherapies 45 found large pre-post effect sizes in depression outcomes (d=0.96, 95% CI: 0.88-1.04), with no differences between CBT and PDT (d=-0.07 in favor of PDT). These results were corroborated by a recent effectiveness study on PDT in chronic depression, which found a large effect size (d=-0.90) in comparison to a waiting list condition 56 . As suggested by one RCT, PDT may be a cost-effective intervention in treatment-resistant depressive disorders as compared to TAU 57 .…”
Section: Secondary Outcomessupporting
confidence: 70%
“…A recent meta-analysis on effectiveness of routinely delivered psychotherapies 45 found large pre-post effect sizes in depression outcomes (d=0.96, 95% CI: 0.88-1.04), with no differences between CBT and PDT (d=-0.07 in favor of PDT). These results were corroborated by a recent effectiveness study on PDT in chronic depression, which found a large effect size (d=-0.90) in comparison to a waiting list condition 56 . As suggested by one RCT, PDT may be a cost-effective intervention in treatment-resistant depressive disorders as compared to TAU 57 .…”
Section: Secondary Outcomessupporting
confidence: 70%
“…However, the treatment assignment was at the discretion of the interviewing clinician and might have been based on other factors such as the patient's interest or group availability. The preliminary analyses did not show differences among the treatments regarding symptomatology, demographics, and treatment outcome, which are further supported by a study with a comparable sample from the same unit conclusion (Eielsen et al, 2022).…”
Section: Methodssupporting
confidence: 57%
“…Short-term psychodynamic psychotherapy (STPP; also called short-term dynamic psychotherapy) refers to a family of short-term psychodynamic therapies that focuses on emotion, including compassion. STPP has proven effective for patients with depression (Abbass et al, 2006; Cuijpers et al, 2008; Driessen et al, 2015), particularly chronic and treatment-resistant depression (Eielsen et al, 2022; Solbakken & Abbass, 2015; Stålsett et al, 2012; Town et al, 2017). Theories of STPP have emotional processes as the core element and conceptualize the relationship between emotions and depression in the context of interpersonal and intrapsychic conflict (e.g., Abbass, 2015; Blagys & Hilsenroth, 2000; Luborsky & Crits-Christoph, 1998; McCullough-Vaillant, 1997).…”
mentioning
confidence: 99%